Penambahan Jumlah Kementerian Negara: Analisis terhadap Efektivitas dan Efisiensi Pemerintahan - Saputro, Bayu; Lubis, Alfi Syahri; Wibowo, Renaldy Wijaksana; Al-Qindi, M. Fariz (UI Scholars Hub, 2025)
The revision of Law 39/2008 on State Ministries, which removes the maximum limit of 34 ministries, has become a polemic issue in society. Analysis shows that increasing the number of ministries is not urgent and runs counter to the spirit of bureaucratic reform. This policy also does not improve the effectiveness of government administration, because the main issue affecting the effectiveness of ministries lies in the quality of ministers, not the number of ministries. The addition of ministries has the potential to cause overlapping authorities, regulatory disharmony, and sectoral egos. From an efficiency perspective, this policy places a heavy burden on the state budget, which is already burdened by Rp. 9000 trillion in national debt, with 45% of state revenue used to pay off debt. In addition, there has been a drastic increase in ministry spending in the Prabowo era compared to the Jokowi era. Keywords: increasing the number of state ministries, Law Number 39 of 2008 concerning state ministries, effectiveness, efficiency